Formação colaborativa reflexiva de professores para o atendimento escolar hospitalar - Pacco, Aline Ferreira Rodrigues (2020)
Education is everyone's right and, therefore, given to those students who are unable to attend regular school due to the hospitalization process or health treatment. Considering the need for this type of service for this portion of the population, the importance of teacher training for teachers to work in hospital classes is highlighted. From these statements, the objectives of this study were: 1) to collaboratively plan, with the coordinators of Special Education, a proposal for teacher training; 2) implement, in a reflective collaborative way, with the Special Education coordinators and with hospital class teachers and Special Education teachers, a teacher training proposal; and 3) to evaluate the reflective collaborative training course from the perspective of teachers in hospital classes and Special Education. The present research consisted of a collaborative character and with a qualitative approach in which 22 professionals participated: three teachers who taught in hospital classes; 14 Special Education teachers, three support teachers (accompanied by target students of Special Education-PAEE in common class); and two Special Education coordinators. The research was carried out in a Teaching Directorate, located in a city in the interior of São Paulo, where a reflective collaborative continuing education course took place. To this end, five face-to-face meetings and five teaching units were held on the Google Classroom online platform. It is noteworthy that, in partnership with the coordinators of the pedagogical nucleus of Special Education, some adjustments were made to enable the organization of the course - considering the demands and possibilities of the researcher, coordinators and teachers. From the analysis of the data, through triangulation, a system of categorization and grouping of the participants' speech reports and responses was elaborated, in addition to the data from the questionnaires and activities. Three major axes were established, namely: course planning; course implementation; and course evaluation. From the experiences shared by the teachers of the hospital classes, the importance of establishing partnerships between the hospital, the hospital class, the family, the student's home school, the school's binding school and the Board of Education became even clearer. . This was because only one establishment would not be able to provide an education service in an environment as complex as the hospital. Thinking about the possibilities of developing practices within the hospital school environment, it was noted that Specialized Individualized Planning (PEI) was a favorable action, both for the student and the teacher. It was taken into account that this type of planning aims to highlight the main needs and potential of the student, something that is essential when the student is ill. It was found that continuing education does not materialize as a solution to educational problems, but, nevertheless, it allows the teacher to improve his actions towards his student. And thus, improve learning conditions and increasing the quality of teaching.